PENDIDIKAN KARAKTER MELALUI PROGRAM PEMBIASAAN DI SD ISLAM TERPADU INSAN UTAMA BANTUL YOGYAKARTA - Dhiniaty Gularso; Khusnul Anso Firoini (TRIHAYU: Jurnal Pendidikan Ke-SD-an, 2016)
Habituation program is a process of formation of attitudes and behaviors that are relatively residential and automatically through the learning process the repeated-over and implemented in out of hour lesson. Habituation is part of education manners with characteristics-feature residential relative, does not require functions thinking enough high, As findings learning experience, Shown in repeated in response to the same stimulus. The research goal is to describe the habituation program that done Integrated Islamic Elementary School (SDIT) Insan Utama hearts educate and form the character of students. SD habituation program in IT personnel consists differences Bantul Main Event Six that routine, spontaneous activity, exemplary activities, programmatic activities, activities of nationalism and outbound learning and training activities.